Nowa emerytura jako element warunkujący godny poziom życia - Klimkiewicz, Aldona (Annales. Etyka w Życiu Gospodarczym, 2011)
One way of showing respect for human dignity is providing people with a suitable level of income security. This respect can be manifested by establishing a certain financial minimum that will allow people to function independently in society and use the opportunities offered by civilisation. The awareness of the above gives special meaning to the level of incomes obtained by the elderly. The fact that pensions are the primary resource for the population to meet its financial needs makes the pension insurance solutions particularly important, especially the formula used for calculating the amount of a future pension. Its final amount will affect the pensioner’s standard of living, enabling them to enjoy the same quality of life they had in the period of economic activity or gradually causing impoverishment. The levels of future pensions depend on factors related to the systemic solutions, but pensioner’s personal characteristics also exert strong influence on their amounts. With the responsibility for having decent incomes after retirement being transferred to the insured themselves, it has become necessary to promote pension awareness (the knowledge of how the new system works) that translates into pension prudence prompting people to reduce voluntarily their current consumption in favour of future consumption. The public need to understand that the income replacement rate will be high only for few of the insured persons, i.e. those boasting high earnings and long, unbroken periods of economic activity. People with poorer records of economic activity will draw lower pensions that will not always allow them to live decent lives after retirement.